Terapi Back Massage untuk Meningkatkan Kualitas Tidur dan Menurunkan Kecemasan Pasien Di ICU - Barkah Waladani; Putra Agina Widyaswara Suwaryo (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Massage can relax muscles, improve blood circulation, reduce pain and anxiety, and improve sleep quality by increasing comfort. However, there is little research on whether back massage improves sleep quality in intensive care unit (ICU) patients. This study investigated the effect of back massage on improving vital signs, sleep quality, anxiety, and depression in ICU patients. This study used a quasi-experimental design with a convenience sampling approach to sample ICU patients. The experimental group received back massages for three consecutive days (n = 20), whereas the control group received usual care (n = 20). The Verran and Snyder-Halpern scales and the Hospital Anxiety and Depression Scale were used, and sleep time was recorded. The effect of the intervention was examined using a generalized estimation equation model with robust standard errors and a time-adjusted exchanMassage can relax muscles, improve blood circulation, reduce pain and anxiety, and improve sleep quality by increasing comfort. However, there is little research on whether back massage improves sleep quality in intensive care unit (ICU) patients. This study investigated the effect of back massage on improving vital signs, sleep quality, anxiety, and depression in ICU patients. This study used a quasi-experimental design with a convenience sampling approach to sample ICU patients. The experimental group received back massages for three consecutive days (n = 20), whereas the control group received usual care (n = 20). The Verran and Snyder-Halpern scales and the Hospital Anxiety and Depression Scale were used, and sleep time was recorded. The effect of the intervention was examined using a generalized estimation equation model with robust standard errors and a time-adjusted exchangeable working correlation matrix. The results showed that the average observed sleep time (measured by nurses) was 39 hours. Back massage improves breathing in patients, improves sleep quality, and causes significant changes in anxiety. These findings indicate that 10 minutes of back massage can improve sleep quality, sleep duration, breathing, and anxiety in ICU patients. The application of back massage shows a positive increase in the sleep quality of ICU patients. Massage training and intervention theory should be further applied when developing critical care nursing courses. geable working correlation matrix. The results showed that the average observed sleep time (measured by nurses) was 39 hours. Back massage improves breathing in patients, improves sleep quality, and causes significant changes in anxiety. These findings indicate that 10 minutes of back massage can improve sleep quality, sleep duration, breathing, and anxiety in ICU patients. The application of back massage shows a positive increase in the sleep quality of ICU patients. Massage training and intervention theory should be further applied when developing critical care nursing courses.